Addressing Human Security in Japan’s Foreign Policy Towards the Developing Countries - Karina Utami Dewi (Global South Review, 2014)
The main purpose of this research is to discuss about Japan’s foreign policy taken in ODA and the decision to have its foreign aid shifted towards more humanitarian issues, such as human security. This research will attempt to answer the question: how does the shift in Japan’s foreign aid influence the recipient countries in terms of Human Security? To measure such influence of policy, this research chose one of the elements in human security, which is health and selected six countries from Asia and Africa as the ODA’s recipient regions. There will be two focuses in this research. First, explaining the reason and the influence of the shift in Japan’s foreign policy to human security. Second, arguing the motivation behind the shift as well as Japan’s actual priority.